Age-Related Variations in Volar Cortical Angle of the Distal Radius. (July 2020) - Gandhi, Rikesh A.; Hesketh, Patrick J.; Bannister, Evan R.; Sebro, Ronnie; Mehta, Samir
Background: The ideal volar locking plate for the treatment of distal radius fracture should anatomically fit the volar surface of the distal radius. The purpose of this study was to measure the volar cortical angle (VCA) of uninjured adult distal radii to determine how well the VCA matches that of modern volar locking plates and whether variations in the VCA are related to demographic factors.Methods: A retrospective radiographic analysis of 273 uninjured adult distal radii was performed. Patients were stratified into age quintiles: less than 27 years, 27 to 43 years, 44 to 51 years, 52 to 64 years, and 65 years or older. The VCA was measured on lateral wrist radiographs, and patient demographics, including age and sex, were collected. Multivariable linear regression analyses were performed to determine the relationship between VCA and demographic factors.Results: The VCA ranged from 23.2° to 42.6°, with a mean of 32.2° ( SD = 3.79). Mean VCA was 32.8 ( SD = 4.17) in the youngest cohort (<27 years) and 30.4 ( SD = 3.63) in the oldest cohort (>65 years). Mean VCA decreased with age, approximately 0.04° per year after adjusting for sex. Men had a 1.6° greater VCA than women after adjusting for age.Conclusion: Mean VCA was greater than the VCA of modern volar locking plates. The VCA decreased with age in both men and women, and men had a greater VCA than women. Such differences must be taken into account to avoid malreduction, tendon irritation, or intra-articular screw placement using current volar plate designs.